Upaya Meningkatkan Hasil Belajar Matematika dengan Metode Penugasan Siswa Kelas VB SD Negeri Model Mataram - Paramitha, Baiq Devy (Lembaga Yasin AlSys, 2022)
The purpose of this study was to determine the increase in learning outcomes of Mathematics with the Assignment Method for Class V.B SD Negeri Mataram Model Even Semester for the 2020/2021 Academic Year. The subjects of this study were students of class V.B SD Negeri Model Mataram, totaling 20 people, consisting of 7 female students and 13 male students. The stages of this research include: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting in each cycle. The results of the study show that the learning outcomes of class VB students at the Mataram Model State Elementary School for the 2020/2021 academic year, using the assignment method can be improved with the final result of the study being the average grade before the action 75.85 or classical completeness 65.00%, to 77 .70 or 75.00% classical completeness in the first cycle, increased to an average of 82.45 or 80.00% in the second cycle and increased to a test average of 91.65 or 100% in the third cycle. From the results of student observations showed that there was an increase in student activity which in the first cycle obtained a score of 18 or 64.29% to 21 or 75.00% in the second cycle and 25 or 89.29% in the third cycle. Increased student activities in learning Mathematics are supported by increased teacher activities in maintaining and improving the learning atmosphere using the assignment method, this can be seen from the observations of teacher activities where in the first cycle a score of 23 or 63.89% was obtained, to 28 or 77.78 % in the second cycle and increased to 32 or 88.89% in the third cycle.